COVID-19: MENGUJI KEBENARAN KONSPIRASI GLOBAL - Mukran H. Usman; Azwar Iskandar; Aswar Aswar (Jurnal Studi Agama dan Masyarakat, 2020)
The research attempted to explain the truth of the assumptions and accusations of some Muslims against the Covid-19 pandemic as a global conspiracy and to refute weak views and arguments related to it. This research applied descriptive qualitative methods using sociological, historical and heuristic approaches. The results showed that the existence of the Covid-19 pandemic as a disease was real, and not a conspiracy issue. The perceptions, arguments and understanding of some Muslims stating that the Covid-19 pandemic was a conspiracy had the potential effect to cause damage the life order as a state and society. In addition, if this understanding was not directed according to the correct Islamic guidance, it was worried that it would have a negative impact on the brotherhood and unity of Muslims. Some baseless assumptions and arguments regarding this epidemic can be answered, refuted and explained with strong and real arguments and evidence based on the hadiths of the Prophet Muhammad, valid narrations, and historical records of Muslims.